2018
DOI: 10.22271/ortho.2018.v4.i4c.26
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of outcome of titanium elastic nailing (TEN) versus hip spica cast in the treatment of femoral shaft fractures in children

Abstract: Femoral shaft fractures are among the most common pediatric injury and treatment of them carries a lot of controversies. The aim of this study was to compare the outcome of titanium elastic nailing versus hip spica cast in femoral shaft fractures in children. This prospective study was conducted on 40 children of 5 to 15 years of age treated with titanium elastic nail or early hip spica cast for the fracture shaft of femur during July 2016 to October 2017 in the Department of Orthopaedics, R.I.M.S., Ranchi, Jh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The demographic detail is provided in table I. 10 With a male to female ratio of 1.9:1, we saw that these kids were overwhelmingly male. Similar male predominance among these children has also been documented by a number of national and international research.…”
Section: Resultsmentioning
confidence: 99%
“…The demographic detail is provided in table I. 10 With a male to female ratio of 1.9:1, we saw that these kids were overwhelmingly male. Similar male predominance among these children has also been documented by a number of national and international research.…”
Section: Resultsmentioning
confidence: 99%
“…This also enhances fracture healing and lessens the risk of infection. Kumar R et al 9 found TEN superior over hip spica, the non-operative procedure carried out in the treatment of diaphyseal femoral fractures in children. Similarly, Shemshaki HR et al 23 found that TEN has advantages over hip spica in their comparative study.…”
Section: Discussionmentioning
confidence: 99%
“…The results were evaluated using Flynn scoring criteria. 9 Routine removal of these implants was recommended 6-9 months after surgery when the fracture line was no longer visible radiologically.…”
Section: Surgical Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…It is relatively uncommon as compared to the adult population, although it's occurrence poses a high burden in morbidity in terms of cost and time of treatment (3). Paediatric femoral shaft fracture affects children's life individually, socially, educationally and emotionally, (4) and also can contribute to long-term disability (5).…”
Section: Introductionmentioning
confidence: 99%